The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1186/1471-2474-12-186
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin substitution in calcitonin deficiency reduces particle-induced osteolysis

Abstract: BackgroundPeriprosthetic osteolysis is a major cause of aseptic loosening in joint arthroplasty. This study investigates the impact of CT (calcitonin) deficiency and CT substitution under in-vivo circumstances on particle-induced osteolysis in Calca -/- mice.MethodsWe used the murine calvarial osteolysis model based on ultra-high molecular weight polyethylene (UHMWPE) particles in 10 C57BL/6J wild-type (WT) mice and twenty Calca -/- mice. The mice were divided into six groups: WT without UHMWPE particles (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
2
15
1
Order By: Relevance
“…However we found no effect of LIR on calcitonin secretion while studies have reported that both Ex-4 and LIR stimulate calcitonin secretion (63,64). Our data are not completely consistent with this mechanism since we observed an increase in resorption surfaces with GLP-1 agonists whereas other studies have reported that calcitonin decreased resorption surfaces (65).…”
Section: Discussioncontrasting
confidence: 99%
“…However we found no effect of LIR on calcitonin secretion while studies have reported that both Ex-4 and LIR stimulate calcitonin secretion (63,64). Our data are not completely consistent with this mechanism since we observed an increase in resorption surfaces with GLP-1 agonists whereas other studies have reported that calcitonin decreased resorption surfaces (65).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the observed reduction in PIO in a-CGRP-deficient mice could have been attributed to a compensatory effect of CT. Huebner et al [16] reported the dual action of CT, as an inhibitor of both bone formation and bone resorption, which could be highly relevant in conditions associated with increased bone resorption, such as PIO. Therefore, further investigations on Calca À/À mice with a combined deficiency in a-CGRP and CT were performed and showed pronounced osteolysis in UHMWPE particle-treated mice at the age of 3 months, while additional substitution of CT in these animals revealed a reduction in PIO [11]. Thus, activation of the CTR could play a crucial role in the PIO process.…”
Section: Introductionmentioning
confidence: 92%
“…In the presence of UHMWPE particles, a reduced http://dx.doi.org/10.1016/j.actbio.2014. 11.051 1742-7061/Ó 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Addition of other agents, including berberine, captropril, dynastat, and N-acetyl-L-cysteine, decreased particle-dependent inflammation and associated osteolysis [14,16,60,61]. In studies taking advantage of knockout mutations, protein replacement of calcitonin and IL-6 increased bone and decreased inflammation, respectively, in calcitonin-negative and IL-6-negative animals [11,19]. The mouse model of osteolysis also allowed agents to be tested locally at the site of the applied particles.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%